PENGEMBANGAN PRODUKTIVITAS MINUMAN KESEHATAN REMPAH-REMPAH MELALUI PEMARUT-PEMERAS JAHE UNTUK MENINGKATKAN IMUN TUBUH - Sutrisno Sutrisno; Mohamad Endy Yulianto; Didik Ariwibowo (Jurnal Pengabdian Vokasi, 2022)
Ginger “Emprit” is a low-cost Indonesian spices with a high antioxidant content. Micro, Small and Medium Enterprises (MSMEs), such as Gendhis Manes in Ungaran, are the main producers of herbal beverage such as instant ginger drinks. In this MSMEs, the traditional method of making instant ginger drink is still used, such as using a manual stirrer instead of a mechanical stirring. The granulator is used to speed up the production process. By using a granulator or sub-critical extractor equipment equipped with photo-pasteurization-uv, this operation tends to increase the productivity of MSME Gendhis Manes.